Tactical decision making in team sports - a model of cognitive processes - Weigel, P.; Raab, M.; Wollny, R. (International Journal of Sports Science, 2015)
In dynamic situations such as sports, athletes use environmental information to compare the current situation with similar situations in the past. On the basis of this experience a recognized option will be generated and chosen [1]. We evaluated decision making in team handball by tracking the eye movements of participants during the decision-making process. We performed two studies using the same sample that differed in the format of visual presentation. In Study 1 we presented different offensive scenes on a virtual tactic board via a computer screen. In Study 2, the participants watched real decision-making situations in a large video projection on a wall. The same participants took part in both studies (i.e., experienced both formats). The studies were intended to extend previous research on the take-the-first heuristic (limited cue use and limited option generation). An option-generation paradigm was used to measure choice behavior in participants with high and low expertise levels. Results of Study 1 showed that all participants produced nearly the same gaze behavior but experts generated options with a higher probability of success. In Study 2 we conceptually validated the effect in more complex situations. Benefits of that information search and choice behavior are explained based on a simple heuristics approach, and practical recommendations are provided.